RISK MANAGEMENT AND FINANCIAL RESILIENCE OF MSMEs : A BIBLIOMETRIC ANALYSIS OF GLOBAL RESEARCH TRENDS - Irviandi Yudhotomo; Gogi Kurniawan; Defi Melandari; Syamsul Arifin (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study aims to map the development of literature on risk management and financial resilience of micro, small, and medium-sized enterprises (MSMEs) using a bibliometric approach. The dataset consists of 71 publications published between 2018 and 2026 and collected from Google Scholar. The analysis was conducted using VOSviewer through keyword co-occurrence, co-citation, and bibliographic coupling techniques. The results indicate a significant increase in publications, particularly after the COVID-19 pandemic. Five major research themes were identified: resilience and entrepreneurial resilience, organizational resilience, risk management and supply chain resilience, crisis and COVID-19, and determinants of MSME resilience. Overlay visualization reveals a shift in research focus from basic risk and resilience concepts toward the integration of risk management, organizational resilience, digital transformation, artificial intelligence, and business sustainability. These findings suggest that MSME resilience is increasingly recognized as a strategic capability for adaptation and long-term business sustainability. This study provides a comprehensive overview of the field and highlights future research opportunities.